2014
DOI: 10.4238/2014.july.24.1
|View full text |Cite
|
Sign up to set email alerts
|

Catheter-directed thrombolysis in the treatment of acute deep venous thrombosis: a meta-analysis

Abstract: ABSTRACT. We performed a meta-analysis for systematic evaluation of the status quo of catheter thrombolysis for the treatment of acute lower limb deep vein thrombosis in China. We searched the China Biomedical bibliographic database (CBM), China National Knowledge Infrastructure (CNKI), Weipu full-text electronic journals, Wanfang full-text database, and Medline (1990 through June 2011) for clinical randomized controlled trials of catheter-directed thrombolysis and superficial venous thrombolysis to compare th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…We identified 3 systematic reviews 119,212,213 and 5 controlled trials (n 5 427). 142,[214][215][216][217] Trials included individuals with objectively confirmed symptomatic proximal DVT.…”
Section: Summary Of the Evidencementioning
confidence: 99%
“…We identified 3 systematic reviews 119,212,213 and 5 controlled trials (n 5 427). 142,[214][215][216][217] Trials included individuals with objectively confirmed symptomatic proximal DVT.…”
Section: Summary Of the Evidencementioning
confidence: 99%
“…The pooled results of five involved comparison studies strengthen the conclusion that the CDT group has a significantly higher patency rate than the anticoagulation group. A previous meta-analysis 48 pooling eight RCTs in China suggested that the effective rate of CDT for the treatment of acute lower extremity DVT was significantly higher than that for superficial venous thrombolysis. The reason was thought to be that thrombolytic drugs can directly act on the thrombolysis site to maximize the activation of plasminogen and effectively dissolve the thrombus.…”
Section: Discussionmentioning
confidence: 99%